Rheological Experimental Analysis Suspensions Based on Glucose Syrup: Characterization of Apparent Rheo-Thickening Mixture - FAGLA, FANOU ZINSOU BENOÎT; AWANTO, CHRISTOPHE; TOUKOUROU, CHAKIROU A.; GRADECK, Michel; BARAVIAN, Christophe; LEBOUCHE, Michel (My University, 2016)
This paper examines the characterization of the carrier fluid in solid-liquid Newtonian suspensions isothermal laminar flow in a horizontal pipe. In Food industry, new products are developed and placed on the consumer market. Many of them are loaded fluids (suspensions) whose flow poses a certain number of problems for researchers. Thus, the current state of knowledge on the hydrodynamics of these Newtonian and Non-Newtonian suspensions does not fully understand the problems related to it, especially if the fluid is loaded with "large spherical hard particles". Currently problems related mainly to loaded flows made of the spherical hard particles of large dimensions (diameter D = 4.4 mm) are complex. The influence of the solid phase made of hard alginate spheres on this flow is critical to the rheology of the carrier fluid. And a rheological experimental analysis of glucose syrup (carrier fluid) showed a change in the behavior of the mixture related to the law of modification of rheology and in the same manner, its hydrodynamics. The study showed that the lateral migration of the particles toward the axis of the pipe in the flow, contributed to this change in the law of behavior of this mixture; this change of Newtonian rheology of suspensions generates the pseudo Non-Newtonian character(the apparent rheothickening type) observed in the carrier fluid.
Keywords: Behaviour; Rheology; Solid-liquid; Suspensions; Particles and Hydrodynamics